2012
DOI: 10.1523/jneurosci.1247-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Brain-Derived Neurotrophic Factor Hampers Inner Hair Cell Synapse Physiology, But Protects against Noise-Induced Hearing Loss

Abstract: The precision of sound information transmitted to the brain depends on the transfer characteristics of the inner hair cell (IHC) ribbon synapse and its multiple contacting auditory fibers. We found that brain derived neurotrophic factor (BDNF) differentially influences IHC characteristics in the intact and injured cochlea. Using conditional knock-out mice (BDNF Pax2 KO) we found that resting membrane potentials, membrane capacitance and resting linear leak conductance of adult BDNF Pax2 KO IHCs showed a normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(127 citation statements)
references
References 72 publications
5
121
1
Order By: Relevance
“…Similarly, ribbons are found in positions other than the synapse in cochlear hair cells of guinea pigs after the post-synaptic fibers are damaged following intracochlear perfusion with 200 μM AMPA (Puel et al, 1995). Furthermore, the number of hair cell ribbons, as assessed by immunohistochemistry, is decreased in brain-derived neurotrophic factor (BDNF)-or Mafb-knockout postnatal mice, where innervation is reduced or delayed (Zuccotti et al, 2012;Yu et al, 2013), and in adult mice when ouabain is applied in the round window causing de-afferentation of cochlear hair cells (Yuan and Chi, 2014). Although these observations were made either with in vitro preparations, such as the cultured cochlea, or in conditions which might affect both the nerve and the hair cells, such as in BDNF mutants and in treated cochlea, these studies suggest that innervation is required for localizing ribbons at the synapse and regulating their number in mechanosensory hair cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ribbons are found in positions other than the synapse in cochlear hair cells of guinea pigs after the post-synaptic fibers are damaged following intracochlear perfusion with 200 μM AMPA (Puel et al, 1995). Furthermore, the number of hair cell ribbons, as assessed by immunohistochemistry, is decreased in brain-derived neurotrophic factor (BDNF)-or Mafb-knockout postnatal mice, where innervation is reduced or delayed (Zuccotti et al, 2012;Yu et al, 2013), and in adult mice when ouabain is applied in the round window causing de-afferentation of cochlear hair cells (Yuan and Chi, 2014). Although these observations were made either with in vitro preparations, such as the cultured cochlea, or in conditions which might affect both the nerve and the hair cells, such as in BDNF mutants and in treated cochlea, these studies suggest that innervation is required for localizing ribbons at the synapse and regulating their number in mechanosensory hair cells.…”
Section: Introductionmentioning
confidence: 99%
“…4 SCs perform many functions, including providing critical trophic factors, preventing excitotoxicity, and mediating regeneration in those systems (non-mammalian vertebrates) capable of replacing lost HCs. [5][6][7][8][9][10][11] When HCs die, SCs also preserve the integrity and function of the remaining tissue by forming scars and clearing dead HCs. 2,[12][13][14][15][16][17] Maintaining a fluid barrier at the surface of the sensory epithelium after damage is necessary to preserve the electro-chemical gradient that drives HC depolarization and therefore sensory transduction after the onset of hearing (reviewed in Wangemann).…”
mentioning
confidence: 99%
“…In conclusion, an increasing number of studies have now demonstrated that the counting of IHC ribbons after hearing loss, for example, in aged specimens [62,64] , or after an acoustic trauma [22,31,32,61,75,76] , or after intake of aminoglycoside [77,78] , can be a first indication of the loss of IHC synapses and AN integrity, independent of (elevated) hearing thresholds.…”
Section: Molecular Biomarker For Dissection Of the Ihc Phenotype And mentioning
confidence: 91%